2022
DOI: 10.1038/s41598-022-17331-8
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells derived extracellular vesicles regulate acquired immune response of lupus mouse in vitro

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease involving multiple systems. Immunopathology believes that abnormal T cell function and excessive production of autoantibodies by B cells are involved in multi-organ damage. Human umbilical cord mesenchymal stem cells (hUCMSCs) therapies have endowed with promise in SLE, while the function of MSC-derived extracellular vesicles (MSC-EVs) was still unclear. Extracellular vesicles (EVs) are subcellular components secreted by a paracellular mechanism and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…They have shown that UC-MSCs exert immunoregulatory effects on SLE, partially mediated by their EVs. UC-MSC-EVs were able to inhibit CD4+ T cells in their model, but lower amounts of TGF-β and IL-17 were found in the supernatant ( 201 ). Another study also using UC-MSC-EVs has shown an amelioration of SLE after EV administration in MRL/lpr mice by inducing M2 macrophages polarization and increasing regulatory T cell ( 202 ).…”
Section: Evs For Diagnosis and Treatment Of Slementioning
confidence: 99%
“…They have shown that UC-MSCs exert immunoregulatory effects on SLE, partially mediated by their EVs. UC-MSC-EVs were able to inhibit CD4+ T cells in their model, but lower amounts of TGF-β and IL-17 were found in the supernatant ( 201 ). Another study also using UC-MSC-EVs has shown an amelioration of SLE after EV administration in MRL/lpr mice by inducing M2 macrophages polarization and increasing regulatory T cell ( 202 ).…”
Section: Evs For Diagnosis and Treatment Of Slementioning
confidence: 99%
“…ROS) through the mitochondrial electron transport chain [ 6 ]. In addition, there are not many related keywords for emerging research directions in recent years, such as mitochondrial DNA (mtDNA) leakage [ 7–9 ], mitochondrial dynamics [ 10 , 11 ], and the role of mitochondria in immunity [ 12 , 13 ]. This reminds us that mitochondria, as organelles, have been noticed by researchers, and the focus has gradually shifted from functional abnormalities to mechanisms and gradually refined in content.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can not only differentiate into various types of cells but also have unique immunomodulatory properties through paracrine signaling or the release of extracellular vesicles, which provides new opportunities for the treatment of autoimmune diseases, such as RA, SLE and in ammatory bowel disease (IBD) [32][33][34][35][36]42]. However, autoimmune diseases do not have a precise pathogenesis, and several studies have reported that the NLRP3 in ammasome is associated with susceptibility, disease severity and treatment effects [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their biological characteristics of low immunogenicity and immune regulation, Huc-MSCs have been widely studied and applied in many autoimmune diseases, such as SLE [32][33][34] and RA [35,36]. However, there have been few reports on the treatment of KD vasculitis with Huc-MSCs.…”
Section: Huc-mscs Inhibit Pyroptosis-related Proteins and Can Improve...mentioning
confidence: 99%